A New Technique for Characterizing Comonomer Distribution in Polyolefins: High-Temperature Thermal Gradient Interaction Chromatography (HT-TGIC) - Cong, Rongjuan; deGroot, Willem; Parrott, Al; Yau, Wallace; Hazlitt, Lonnie; Brown, Ray; Miller, Matt; Zhou, Zhe (Macromolecules, 2011)
This paper documents a new polyolefin characterization technique, high-temperature thermal gradient interaction chromatography (HT-TGIC or TGIC), to quantify comonomer distribution. A set of homogeneous ethylene−octene homopolymers are used with a commercially available column having a graphitic substrate (HYPERCARB) to demonstrate this technique’s applicability to fractionating polyolefins. The separation mechanism appears to be based on the interaction of the polyolefin chains with the graphite surface upon a temperature change in an isocratic solvent. The TGIC technique overcomes the key issues encountered in crystallization based techniques and in high-temperature liquid chromatography with a solvent gradient (HT-LC). Crystallization based techniques cover only a narrow analysis range of 0−9 mol % comonomer content and suffer from potential error in the analysis caused by cocrystallization effects. HT-LC is limited in its capability because of the limited choice in detectors available. Conversely, TGIC, because of the simplicity in solvent composition, has many commercially available detectors, such as infrared detectors (IR), light scattering detectors (LS), and viscometer detectors. For example, a triple detector TGIC with online IR, LS, and viscometer not only is capable of providing comonomer content and distribution from its TGIC retention temperature profile but also can provide a comprehensive microstructure mapping of molecular weight (MW) and intrinsic viscosity (IV) across the comonomer distribution. Under the experimental conditions used in this study, all these features can be obtained in a short analysis time of less than 1 h, for a comonomer content range of from 0 to 50 mol %. Additionally, TGIC is not subject to the cocrystallization problems that traditional polyolefins comonomer distribution characterization techniques have.